18F‐Labeled Derivatives of Irbesartan for Angiotensin II Receptor PET Imaging. (15th November 2018) - Hoffmann, Matthias; Chen, Xinyu; Hirano, Mitsuru; Arimitsu, Kenji; Kimura, Hiroyuki; Higuchi, Takahiro; Decker, Michael
Abstract: The renin angiotensin aldosterone system (RAAS) is a hormonal cascade involved in the regulation of blood pressure and electrolyte balance, and represents a common target for the treatment of various diseases including hypertension, heart failure, and diabetes. Herein we present a novel 18 F‐labeled derivative of the drug irbesartan, one of the most prescribed angiotensin II type 1 receptor (AT1 R) antagonists, for in vivo positron emission tomography (PET). This allows the in vivo measurement of AT1 R expression, and thus the evaluation of functional changes in its expression under pathophysiological conditions. We followed various synthetic approaches optimized for the introduction of fluorine into different positions of the aliphatic side chain of irbesartan. Radioligand binding studies revealed that fluorine atoms at specified positions (α‐position (IC50 =6.6 nm ) and δ‐position (IC50 =8.5 nm ) of the aliphatic side chain) do not alter the binding properties of irbesartan (IC50 =1.6 nm ). After successful radiolabeling with fluorine‐18 in a radiochemical yield of 11 %, we observed high renal uptake in healthy rats and pigs, which could be decreased by pretreatment with the parent compound irbesartan. Abstract : An eye on the kidneys : Novel fluorinated derivatives of irbesartan were synthesized, and the synthesis of suitable precursor molecules for positron emission tomography, including radiolabeling with fluorine‐18, was achieved. In vitro binding and renal imaging studies in rats and pigs reveal the excellent performance of these radiotracers for renal imaging.